Analisis Strategi dan Hambatan Pemasaran di Perumda Tirtanadi Cabang Diski - Tri Nurhayati, Sucinta; Aisyah, Siti (Program Studi Manajemen, Fakultas Ekonomi, Universitas Islam Majapahit, Jawa Timur, Indonesia, 2024)
Regional Drinking Water Company (Perumda) Tirtanadi Diski Branch operates in the clean water supply industry, not only plays a role in meeting the basic needs of the community, but also contributes to sustainable development and public health. Marketing strategy is the first step before carrying out marketing activities. Marketing strategy is a fundamental element in the success of an organisation, especially in an era of increasingly complex global competition. Marketing is not only limited to promotional activities, but involves a deep understanding of consumer needs, appropriate product design, effective distribution, and efforts to create sustainable value. Marketing is not only considered a function, but also a strategic business concept. Therefore, marketing strategy must consider all environmental factors, both internal and external, that affect the company. This study aims to analyse the marketing strategies implemented by Perumda Tirtanadi Diski Branch in providing clean water services to the community, as well as identify the obstacles faced in its implementation. Using a qualitative descriptive method, data was collected through observation, interviews with marketing staff, and analysis of internal company documents. The results showed that Perumda Tirtanadi implements a customer relationship-based marketing strategy with a community-based approach and local promotions, which effectively increases customer loyalty. However, the main challenges faced include limited distribution infrastructure, limited budget, competition with alternative water sources, and lack of public awareness regarding the importance of water conservation. This research suggests that Perumda Tirtanadi should improve its infrastructure, increase its community education campaigns, and find solutions to optimise its budget and face competition. With more innovative and responsive marketing strategies, Perumda Tirtanadi can strengthen its position as a reliable and affordable water provider for the community.